Correlation of 15-prostagladin dehydrogenase expression with clinicopathological factors and survival rate in gastric adenocarcinoma. (January 2015) - Seo, Sang Hyuk; Kang, Mi Seon; Kim, Kwang Hee; An, Min Sung; Ha, Tae Kwun; Bae, Ki Beom; Oh, Min Kyung; Choi, Chang Soo; Oh, Sang Hoon; Choi, Young Kil
Abstract: Introduction : The prostaglandin (PG) E2 level, which is associated with oncogenesis, progression and metastasis in various types of cancer, is determined by reciprocal regulation of 15-prostaglandin dehydrogenase (15-PGDH) and cyclooxygenase-2. This study investigated 15-PGDH expression in gastric adenocarcinoma, the associations between 15-PGDH expression and clinicopathological factors, and the correlation between 15-PGDH expression and the 5-year gastric-cancer-specific survival rate (5-year GCSS).Methods : From 175 patients who underwent gastrectomy, we obtained biopsies of gastric adenocarcinoma tissues and adjacent normal tissues for preparation as formalin-fixed, paraffin-embedded specimens and conducted an immunohistochemical analysis.Results : 15-PGDH expression was low in 65.1% of cases. 15-PGDH expression showed no relationship with age or gender, but was significantly correlated with the pathologic type, T stage, N stage, TNM stage, positive lymph node metastasis, metastasis to a larger quantity of lymph nodes, positive lymphatic invasion, positive vascular invasion, positive perineural invasion, and palliative gastrectomy. The 5-year GCSS of the low-expression group was 77.19% and a lower level of 15-PGDH expression correlated to a lower 5-year GCSS. 15-PGDH expression significantly influenced the 5-year GCSS on univariate but not multivariate analysis.Conclusion : Our findings indicate that 15-PGDH expression was low in gastric adenocarcinoma and was correlated with the clinicopathological factors associated with prognosis and a more advanced stage of gastric adenocarcinoma. Also, 15-PGDH expression was significantly associated with the 5-year GCSS, but was not an independent prognostic factor thereof. Highlights: 15-PGDH was low expression in gastric cancer. 15-PGDH expression was related to progonstic factor and severe stage in gastric cancer. 15-PGDH expression was related to survival rate in gastric cancer but was not independent prognostic factor.